Loss and Gain in English Subtitle Translation of Tilik Movie’s Culture-specific Items - Annisa Nurul Firdausi; Teguh Setiawan (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2022)
Abstract. Culture-specific item or CSIs are languages unique features which differentiate a language to another. The Javanese language and English are two languages which has a big gap in the lexical, social, and cultural. In producing the translation from Javanese to English and vice versa, the translator must consider a lot of things mainly the CSIs feature of the text to avoid a misleading information. The equivalence of SL to TL must met so that the audience get the exact information that the writer in SL wants to employ. This study aims to analyze the cultural loss and gain in some words related to the words in ST and TT in order to see the significance of those words to each of the language. The language used in this movie is Javanese language with English subtitle. This study applied descriptive qualitative research methodology which does not use any numerical data counting. Documentation, transcription, and note-taking are used to collect the data. This study used Aixelá’s term of CSIs and applied Newmark’s categorization of CSIs. Five categories are found in the data of the study which has ecology with geographical features, material cultures with time, social culture with addressing term, social norm, social activity and religious term, organization with political term, and gestures and habit with interjection and politeness manner. The loss and gain in the translation is bound to happen, to cope with the loss and gain, reduction, addition, generalization, compensation, and deletion is used by the translator. Keywords: Culture-Specific Items, Tilik, Loss, Gain, Translation